Multiparameteranalyse mittels Radionuklidventrikulographie in der Beurteilung der linksventrikulären Funktion nach Herztransplantation - Hartmann, A.; Klepzig, H.; Standke, R.; Olbrich, H. G.; Cieslinski, G.; Kober, G.; Baew-Christow, T.; Maul, F. D.; Hör, G.; Satter, R; Kaltenbach, M. (Nuklearmedizin - NuclearMedicine, 1991)
Left ventricular systolic and diastolic performance was evaluated by radionuclide angiography in 17 patients following cardiac transplantation and compared with normal persons. Both groups performed supine bicycle exercise during the investigation, the control group at 102 ± 73 W and the transplanted patients at 61.2 ± 15 W. The ejection fraction increased in the normal persons from 61 ± 8 to 69 ± 10% whereas in the transplanted patients it did not increase significantly. There were no relevant changes in systolic parameters during exercise in the transplant recipients. The changes in diastolic parameters were significantly smaller in transplant patients than in normals. After correction for heart rate-induced changes a significantly different time course of the systolic-diastolic sequence during the cardiac cycle became evident in the transplanted group at rest. During exercise the systolic-diastolic sequence during the cardiac cycle became similar in both groups. It is concluded that the reduced exercise capacity of patients in the late phase after cardiac transplantation is partially due to the absence of an EF increase and a limitation of diastolic reserve during exercise.